THE RELATIONSHIP BETWEEN EMOTIONAL EATING, MEAL SKIPPING AND UNHEALTHY FOOD CONSUMPTION PATTERN IN ADOLESCENT GIRLS - Nisri Ina Zahrah; Moh Fanani; Tonang Dwi Ardyanto (The Indonesian Journal of Public Health, 2023)
Introduction: Psychological problems can lead to emotional eating and meal skipping, which may impact unhealthy food consumption patterns. This study aimed to assess the interrelationship between emotional eating, meal skipping, and unhealthy food consumption pattern in adolescent girls. Method: This cross-sectional study included 122 samples of adolescent girls aged 13-15 years. The study was carried out in Tangerang, in June 2021. The data of emotional eating were measured by Emotional Eater Questionnaire (EEQ), meal skipping collected by self-reported questionnaire of daily eating frequency, and unhealthy food consumption patterns measured by Food Frequency Questionnaires (FFQ). Result: The results showed majority of emotional eater subjects more often consumed fatty foods (76.6%). It’s also found that adolescents  skipping breakfast were high in consumed sweet  foods (66.0%), while those skipping lunch (63.6%) and dinner (54.5%) were found higher to consume  fatty foods than others. In addition, multivariate regression analyses showed that simultaneously between the variables, only emotional eating variables had a significant  relationship with unhealthy food consumption patterns (p-value = 0.002), while meal skipping variables were not significantly related. Conclusion: It can be concluded that emotional eating can affect unhealthy food consumption patterns among adolescent girls, while meal skipping did not show  any meaningful effect.